Gambaran Kejadian Wabah Diare dan Faktor-faktor Terkait di Dusun Senden Desa Sidorejo Kecamatan Lendah Kabupaten Kulon Progo tahun 2005 - - Kusbaryanto; Titik Hidayati (Universitas Muhammadiyah Yogyakarta, 2008)
In Indonesia diarrhea is still a leading health problem because it causes extraordinary occurrence of illness followed by death. Thus, epidemiological study of diarrhea needs to be conducted. This study aimed to obtain a description of extraordinary occurrence of diarrhea and its related factors in Senden hamlet, Sidorejo, Lendah, Kulon Progo. This study was a total survey with an epidemiological explorative approach. Definite diagnosis was based on clinical symptoms found during detection and the etiology was confirmed by laboratory analysis of the water sample used by patients and patients’ stools. Primary data of patient was obtained through a total survey to find cases using a questionnaire. Case finding was done based on the report from a local community health center, followed by new cases finding consisting of name, sex, age, address, occupation, factors related with the occurrence of disease and history of illness. Secondary data was taken from the report of patient visit to community health center. Data was analyzed descriptively. The study was conducted in Senden hamlet, Sidorejo, Lendah, Kulon Progo on 20 November to 5 December 2005. Fifty patients were diagnosed to have diarrhea in Senden. From 50 diarrhea patients, 98% had nausea and vomiting, 96% with headache, 90% with epigastric pain, 72% with fever, 66% with mucous diarrhea, 56% with cold sweats and 26% with bloody mucous diarrhea. Attack Rate of diarrhea was 22.6%. The highest occurrence of diarrhea was at age of45-59 years old (33.93%) and the lowest occurrence at 0-4years old (1.78%). The area having most cases was sub-hamlet 57 (RT57) (82%). Based on the time of extraordinary occurrence of illness, the epidemic curve developed was a common source type. The cause of diarrhea was coliform bacteria. The most possible source and mode of transmission of diarrhea was drinking water contaminated with coliform bacterium through faeces. Factors related with the extraordinary occurrence of diarrhea in Senden included poor environmental sanitation and unhygienic people ’s behavior such as defecating in any places and not washing hands before eating.Di Indonesia penyakit diare masih merupakan masalah kesehatan utama karena masih sering menimbulkan KLB dengan disertai kematian. Untuk itu perlu dilakukan suatu penelitian epidemiologi penyakit diare. Penelitian ini bertujuan untuk mendapatkan gambaran kejadian luar biasa diare beserta faktor-faktor yang terkait di dusun Senden, Sidorejo, Lendah, Kulon Progo. Penelitian ini merupakan survei total dengan pendekatan epidemiologis eksploratif. Kepastian diagnosis didasarkan atas gejala klinis yang didapat selama pelacakan dan untuk mengetahui etiologi dilakukan pemeriksaan laboratorium terhadap sampel air yang digunakan maupun tinja penderita. Data primer penderita diperoleh dengan menggunakan kuesioner. Pelacakan kasus dicari berdasarkan laporan Puskesmas setempat dilanjutkan dengan mencari kasus baru, meliputi nama, jenis kelamin, umur alamat, pekerjaan, faktor-faktor yang berhubungan dengan terjadinya penyakit dan riwayat penyakit. Data sekunder diambil dari catatan data kunjungan Puskesmas. Data dianalisis secara deskriptif. Penelitian dilaksanakan di dusun Senden, Sidorejo, Lendah, Kulon progo pada 20 November - 5 Desember 2005. Penduduk dusun Senden yang didiagnosis diare sebanyak 50 orang. Dari 50 penderita diare, 98% mempunyai keluhan mual muntah, 96% dengan pusing, 90% dengan nyeri perut, 72% dengan demam, 66% dengan diare lendir, 56% dengan keringat dingin dan 26% dengan diare lendir darah. Attack rate diare 22,6%. Kejadian diare paling banyak pada usia 45-59 tahun (33,93%) sedangkan yang terkecil pada golongan umur 0-4 tahun (1,78%). Daerah yang paling banyak mengalami daerah adalah RT 57 (82%). Berdasarkan waktu kejadian KLB menunjukkan bahwa kurva epidemik yang terbentuk adalah tipe common source. Penyebab diare adalah bakteri koliform. Sumber dan cara penularan diare kemungkinan besar melalui sumber air minum yang terkontaminasi oleh bakteri coliform. Faktor-faktor yang berhubungan dengan kejadian KLB diare di dusun Senden antara lain sanitasi lingkungan yang belum baik dan perilaku penduduk yang kurang menjaga higienis misalnya buang air besar di sembarang tempat, tidak cuci tangan sebelum makan.